2019
DOI: 10.2147/jbm.s203828
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effects of Hydroxyurea Therapy on the Six-Minute Walk Distance in Patients with Adult Sickle Cell Anemia: An Echocardiographic Study</p>

Abstract: Background: The impact of hydroxyurea (HU) medication as treatment of choice has not been evaluated in adult sickle cell anemia (SCA) patients in terms of the 6-min walk distance (6 MWD). Aim: The aim of the study was evaluating the effects of HU on the 6 MWD, serum brain natriuretic peptide (NT-pro BNP) level, and pulmonary hypertension (PH) measured by tricuspid regurgitation velocity (TRV). Methods: In this cross-sectional, prospective study, 110 patients with homozygous SCA were studied and compared with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Figure 2 d shows the measurement of Tricuspid regurgitant velocities in SCD patients [ 50 , 61 66 ]. The pooled estimates show a significant reduction in TRV post-hydroxyurea treatment with a standardized mean difference of – 1.37(CI − 2·31, − 0.42; p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 d shows the measurement of Tricuspid regurgitant velocities in SCD patients [ 50 , 61 66 ]. The pooled estimates show a significant reduction in TRV post-hydroxyurea treatment with a standardized mean difference of – 1.37(CI − 2·31, − 0.42; p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…Post hydroxyurea therapy of 20 mg/kg/day, 2(6.9%) developed new AVN. Five (50%) of SCD patients who were on hydroxyurea for more than 5 years had the worst AVN hip joint [ 66 , 67 ]. In another prospective study by Kris M. Mahadeo et al among 257 SCD patients screened for osteonecrosis of the femoral head, the prevalence of avascular necrosis of the hip joint who were on hydroxyurea therapy was 18(21.68%) which was higher compared to the prevalence of AVN who were not on hydroxyurea therapy 8(8.08%) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is conflicting data regarding the effect of disease‐modifying therapies (DMT) on diastolic function 13–15,30–32 . While some studies showed hydroxyurea therapy 15,30 or monthly erythrocyte transfusions 14 to be associated with less diastolic dysfunction, other studies did not replicate it 13,14,31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…6,29 There is conflicting data regarding the effect of disease-modifying therapies (DMT) on diastolic function. [13][14][15][30][31][32] While some studies showed hydroxyurea therapy 15,30 or monthly erythrocyte transfusions 14 to be associated with less diastolic dysfunction, other studies did not replicate it. 13,14,31,32 However, most prior studies were limited by their cross-sectional design, small sample size, selection bias, nonuniform duration of treatment with disease-modifying therapies, and concomitant use of other clinical therapies, confounding the outcomes.…”
mentioning
confidence: 99%